Student Business Incubation by Academic Programs: An Exploratory Study - Pertiwi, Imanda Firmantyas Putri; Trishananto, Yudha (Journal of Business and Management Review, 2024)
Research Aims: This study aims to serve as a preliminary step in developing a business incubation program for the sharia business management department at UIN Salatiga. As the first step, this research will map the potential of tenants, tenant needs, parties that can support tenant business success, opportunities and challenges, and the framework for establishing the sharia business management business incubator. Design/methodology/approach: This research employs a qualitative method, with data collected through interviews with the academic community of the Sharia Business Management Program. In addition to in-depth interviews, this study also conducts Focus Group Discussions (FGD). A saturated sample will be the choice for this research. Based on observations and distribution of participant registration questionnaires, it was found that 47 students registered their businesses for incubation. Research Findings: This research found that comparative studies with business incubators at other universities provide important insights into best practices that can be adopted by the sharia business management Program. A collaborative approach with stakeholders, such as government agencies and partner universities, as well as infrastructure support from internal parties, offers great opportunities for developing an effective business incubator at UIN Salatiga. Theoretical Contribution/Originality: The theoretical contribution of this study lies in the application of the business incubation concept, which has been more commonly used in general universities, and is now adopted and developed in the context of sharia business education. This research provides a specific model of how business incubation can be implemented in an educational environment that focuses on sharia values. Overall, this study offers a new and more detailed model of business incubation in the context of sharia education, which can serve as a reference for developing similar incubators at other universities